An alternative approach to predict Seebeck coefficients: Application to La3−xTe4. (August 2019) - Wang, Yi; Chong, Xiaoyu; Hu, Yong-Jie; Shang, Shun-Li; Drymiotis, Fivos R.; Firdosy, Samad A.; Star, Kurt E.; Fleurial, Jean-Pierre; Ravi, Vilupanur A.; Chen, Long-Qing; Liu, Zi-Kui
Abstract: A thermodynamic understanding of Seebeck coefficient was demonstrated in terms of electrochemical potential. It divided the contributions to the Seebeck coefficient into two contributions: the effect of thermal electronic excitations due to Fermi distribution and the effect of charge carrier gradient due to thermal expansion. The procedure is illustrated within the rigid band approximation in terms of the electronic density-of-states and the quasiharmonic approximation in terms of the phonon density-of-states. Numerical results were given using the n -type high temperature thermoelectric material La3- x Te4 at x = 0, 0.25, and 0.33 as the prototype at a variety of carrier concentrations. Graphical abstract: Unlabelled Image